USE OF VENN DIAGRAM POSSIBILITIES IN ORGANIZATION OF LESSONS OF THEORETICAL MECHANICS - Mahmudov Zokirjon Sotivoldievich; Raximov Abdulvoris Mutalovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The mentioned article talks about the issue of using Venn diagrams in lectures and practical classes on theoretical mechanics.